ANTIBIOTIKA RASIONAL DALAM ILMU BEDAH - Sander, Mochamad Aleq (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2012)
Utilizing of antibiotics to cure operation infection actually not differ from gift antibiotics in general. The difference was antibiotic treatment be addition therapy after surgery. The aim of antibiotics treatment was prevent or cure infection by reducing or eliminating bacteria until human body can handle this pathogenic organism.